Pengembangan Instrumen Penilaian Tingkat Pengetahuan, Sikap, Dan Perilaku Swamedikasi Batuk Versi Bahasa Indonesia - Maria, Nisa; Apriani, Elvina; Sari, Kartika Citra Dewi Permata (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Cough is a symptom that people often treat with self-medication. Self-medication practice can be formed from knowledge and attitudes. The development of this instrument aimed to obtain a valid and reliable Indonesian language questionnaire to measure the level and relationship of knowledge, attitudes, and cough self-medication practice in adult patients. The questionnaire was prepared based on literature studies and developed by the Dagusibu concept and cough management. Three pharmacists from academia and the community became validators in the face and content validation test. Construct validation and reliability tests were obtained from 30 adult respondents who had carried out cough self-medication in Jabodetabek. Content validation was carried out in 2 stages. The results of the first stage test had an S-CVI score of 0.93, with 26 questions having an I-CVI value <0.79, so stage 2 validation was carried out, which met the I-CVI and S-CVI scores. The total number of questions from content validation was 143, divided into 6 parts. The final questionnaire had 137 questions consisting of sections A-B (8 questions) for personal and sociodemographic data; part C (30 questions) related to self-medication profile; part D (36 questions) about knowledge with a 3-point Guttman scale; part E (30 questions) related to attitudes with a 5-point Likert scale; and part F (33 questions) about behavior with a 2-point Guttman scale. The final questionnaire met the criteria of validity and reliability and could be filled in independently by respondents in Indonesia.